2021
DOI: 10.1016/j.injury.2021.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Implant failure after externally magnetic-controlled nail lengthening

Abstract: The number of intramedullary procedures to treat leg length discrepancy (LLD) has risen in the past decade and this has led to increased complications such as nail breakage. The aim of this study was to reveal our experience with implant failure after externally magnetic-controlled telescopic bone lengthening. We observed nail-breakage in 4 out of 24 patients (16.7%) after 6 to 15 months (median 13.5 months) following lower limb lengthening for LLD due to non-union or insufficient bone healing. Three femora an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Bending occurred during both lengthening and consolidation. In multiple studies, the authors reported premature weight-bearing as the likely reason [13][14][15] . We found the rate of noncompliance regarding weight-bearing in the cases with failure to be 18% (7 of 40), with breakage of distal locking screws as the most frequently observed mechanical failure.…”
Section: Discussionmentioning
confidence: 99%
“…Bending occurred during both lengthening and consolidation. In multiple studies, the authors reported premature weight-bearing as the likely reason [13][14][15] . We found the rate of noncompliance regarding weight-bearing in the cases with failure to be 18% (7 of 40), with breakage of distal locking screws as the most frequently observed mechanical failure.…”
Section: Discussionmentioning
confidence: 99%
“…Shabtai et al reported on the successful treatment of congenital limb deficiency with PRECICE nails with minimal complications [19] . Nevertheless, some retrospective studies have reported complications such as non-union necessitating revision surgery [20] , mechanical failure [21] , and nail breakage [22] , one of which occurred 15 months after implantation [23] . Tiefenböck et al reported a complication rate of 70%, nevertheless, 30% of complications were reported in patients with a congenital deformity [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Planning revision surgery (involving replacing the nail) at an earlier stage can help avoid nail breakage. Additionally, extracting an intact implant is much easier, more cost-effective, and carries less risk when performed sooner [42].…”
Section: Future Perspectivesmentioning
confidence: 99%